The Fragmentation of Sápmi: A Nordic Model of Settler Colonialism - McGuire, Lynette (Scandinavian-Canadian Studies, 2022)
While the Nordic countries are frequently renowned as some of the most peaceful societies in the world, such a conception of peace cannot fully encapsulate the experiences of the Sámi. Likewise, the global movement toward settler-Indigenous reconciliation since the 1960s has set the Nordic response apart from the rest of the world. Building upon existing understandings of internal colonialism and structural violence, this paper analyzes how pragmatic attempts by Finland, Norway, and Sweden to reconcile with the Sápmi have constituted a unified Nordic model of continued settler colonialism, as well as how differences between the National Sámi parliaments contribute to that model. Finally, this paper examines the impact that the Nordic model of settler colonialism has had on pan-Sámi politics, particularly concerning problems of Sámi reunification since the fall of the Soviet Union. Bien que les pays nordiques aient la réputation de faire partie des sociétés les plus paisibles du monde, cette vision de paix n’intègre pas totalement les expériences des Samis. De la même façon, la tendance internationale vers la réconciliation entre colons et peuples autochtones depuis les années 1960 a mis la réponse nordique à part du reste du monde. En se basant sur la compréhension actuelle du colonialisme interne et de la violence structurelle, cet article analyse comment les tentatives pragmatiques de la Finlande, la Norvège et la Suède pour se réconcilier avec le Sámi ont établi un modèle nordique uniforme continuant le colonialisme de peuplement, et comment la disparité des parlements nationaux Sami contribuent à ce modèle. Enfin, cet article examine l’impact que le modèle colonial nordique a eu sur les politiques pan-samies, particulièrement en ce qui concerne les problèmes de la réunification samie depuis la chute de l’URSS.